"Lambda‐wave" ST‐elevation is associated with severe prognosis in stress (takotsubo) cardiomyopathy. Issue 6 (9th July 2018) - Tarantino, Nicola; Santoro, Francesco; Guastafierro, Francesca; Di Martino, Luigi F. M.; Scarcia, Maria; Ieva, Riccardo; Ruggiero, Antonio; Cuculo, Andrea; Mariano, Enrica; Di Biase, Matteo; Brunetti, Natale Daniele
Abstract: Background: Persistent ST‐segment elevation in acute coronary syndrome is associated with both short and long‐term complications. By contrast, there is limited information about ST‐elevation and its evolution during takotsubo (stress) cardiomyopathy (TTC). Aim: To evaluate whether persistent downsloping ST‐elevation in the early stages of TTC might correlate with short and long‐term clinical events. Methods: One‐hundred fifty‐eight consecutive subjects with TTC were prospectively enrolled and assessed by electrocardiogram. Patients were classified in two groups according to the presence of downsloping ST‐elevation ≥5 mm lasting at least 24 hr ("lambda‐wave" ST‐elevation group vs. without downsloping ST‐elevation) in at least one/two contiguous leads. Results: Five (3.2%) patients, all female with a mean left ventricular ejection fraction 32 ± 5%, were included in the lambda‐wave ST‐elevation group. These patients were characterized by a higher prevalence of physical stressor (100% vs. 49%, p  = 0.04) and higher admission and peak levels of troponin‐I levels during hospitalization. Peak of ST‐elevation in the lambda‐wave ST‐elevation group was reached 6 hr after admission and gradually decreased after 24 hr. In‐hospital complications were observed in all the patients presenting lambda ST‐elevation (100% vs. 23%, p  = 0.03, OR: 29.1, p  = 0.04); one patient presented endoventricular thrombosis and two died of cardiogenic shock. At long‐term follow‐up (mean 443 days), adverse events were observed in 80% of patients with lambda‐wave ST‐elevation (RR of adverse events at follow‐up 32, p  < 0.01). Conclusion: Persistent downsloping lambda‐wave ST‐elevation during the acute phase of stress cardiomyopathy may be associated with a higher risk of adverse events at short and long‐term follow‐up.